2019
DOI: 10.1002/jppr.1533
|View full text |Cite
|
Sign up to set email alerts
|

Utility of PhaSeal, a closed‐system drug transfer device, in facilitating vial sharing to reduce waste and assist in medication cost savings

Abstract: Background The cost of cancer care is rising. With the soaring costs of cancer treatment, strategies to minimise medication wastage have become more important. Aim This study evaluated cost savings associated with a centralised pharmacy aseptic service using the closed‐system drug transfer device PhaSeal (Becton, Dickinson and Company, North Ryde, NSW, Australia) for the preparation of monoclonal antibodies (mAbs) in a large teaching hospital. Methods Two scenarios for the preparation of mAb were evaluated ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Using CSTD will introduce some new risks, and traditional vial-sharing will also require manual intervention for their storage, which could result in the incorrect writing of information or dose miscalculation or omission altogether ( 21 ). Rather than use CSTDs to store drugs for reuse in the same period ( 22 ), we prepared them simultaneously by employing an intelligent dispensing robot. Therefore, the introduction of an intelligent robot capable of dispensing multiple prescriptions simultaneously to run a real-time vial-sharing strategy in this investigation encountered not the traditional approach-related safety issue concerns, such as the introduction of impurities due to repeated interspersing or recording drug information incorrectly.…”
Section: Discussionmentioning
confidence: 99%
“…Using CSTD will introduce some new risks, and traditional vial-sharing will also require manual intervention for their storage, which could result in the incorrect writing of information or dose miscalculation or omission altogether ( 21 ). Rather than use CSTDs to store drugs for reuse in the same period ( 22 ), we prepared them simultaneously by employing an intelligent dispensing robot. Therefore, the introduction of an intelligent robot capable of dispensing multiple prescriptions simultaneously to run a real-time vial-sharing strategy in this investigation encountered not the traditional approach-related safety issue concerns, such as the introduction of impurities due to repeated interspersing or recording drug information incorrectly.…”
Section: Discussionmentioning
confidence: 99%
“…4 Recently, in a two year retrospective review from a major Australian hospital, Siderov demonstrated yearly savings of US$3,52,500 with vial sharing using a CSTD to extend BUD up to 7 days. 6…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently, in a two year retrospective review from a major Australian hospital, Siderov demonstrated yearly savings of US$3,52,500 with vial sharing using a CSTD to extend BUD up to 7 days. 6 The lack of reliable stability data on prepared parenteral products can commonly limit the shelf life of these products to 24 hours resulting in potential waste if these products are not administered in time. Pharmaceutical compounding companies perform inhouse stability studies, thus enabling them to extend the shelf life on prepared parenteral products and allowing them to be reused up until their expiry date.…”
Section: Introductionmentioning
confidence: 99%